Study on the feasibility of use of hydrochloric acid as an alternative to sulphur dioxide for preserving longan - Apai, Wittaya; Klongdee, Hatairat; Sukhvibul, Nipat; Noppakoonwong, Uthai; Shan, Lim Shwu; Cheng, Luk Seow; Alice, Tan Swee Chuan; Yu, Neo Shan; Hoon, Khoo Gek; Lee, Ching Ai; Amareok, Sanong; Rattanakam, Sittipong; et al. (Food and Applied Bioscience Journal, 2017)
HCl as possible alternative to SO2 in fresh longans for export was investigated. Fruit was exported from Thailand and transported to Singapore for fruit quality assessment, i.e. sensory evaluation, HCl acid residue test and shelf life evaluation. The 1st set was treated on 8th July 2013 and had 3 treatments comprising of 4 baskets as replication for each treatment. 11.5 kg of fruits in basket were dipped in a plastic bucket containing 60 L of 6.4% HCl solution+1%NaCl+0.1%Tween 20 (wetting agent) for 5 min and these were allowed to air dry for 2 h. (T1). This was compared with SO2 (T2) and untreated fruit (T3) treatments. An additional HCl treatment using HCl dipping machine at the same concentration (T4) comprising of 6 baskets was done on 12th July 2013. All 18 baskets from the two sets were transported on 12th July 2013 and arrived at the Post-Harvest Technology Center (PHTC) of Agri-Food & Veterinary Authority (AVA) in Singapore on 19th July 2013. The fruit was stored further at 5°C with 76–96% RH for 20 days. The results found that both HCl treatments (T1, T4) and SO2 (T2) prevented pericarp browning during storage when evaluated from browning index and pericarp acceptance and fruit decay as compared with untreated fruit (T3). The sensory acceptance of flesh appearance, firmness and taste of HCl (T1, T4) during cold storage showed good result and no significant difference. HCl residue in fruit flesh from two HCl treatments was shown at low value from 0.000 to 0.006% (flesh pH 6.78–7.03) during storage. The fruits dipping in HCl (T1) and (T4), SO2 (T2) and untreated fruit (T3) could prolong storage life for 25, 27, 31 and 12 days respectively at 5°C, 76–96% RH followed by 3 days ambient storage to simulate display for sale at ambient conditions, thus their shelf life were long enough for export.